(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Social medicine is a segment of public health services aiming to improve the population’s health through various preventive programmes and activities. This is why the metrics of performance measurement can be a challenge, because these are activities with a qualitative outcome that requires a time lag. The research subject is the assessment of effectiveness of social medicine programmes implemented in the public health system of the Republic of Croatia. For this empirical research, data were used by the county’s Teaching Institute of Public Health, Social Medicine Department. The department has three basic objectives: to assess the health and health needs of the population, to develop public health policy, and to ensure the implementation of effective programmes. The aim of this research is to find the metrics that will be useful for the final outcome assessment of social medicine activities. The theory and the concept of the Balanced Scorecard (BSC) are relevant for the field of health care, but there is not much research on applying the BSC in preventive activities, especially those in the field of social medicine. Adjusted Balanced Scorecard is proposed for improving the effectiveness of performance assessment of current and future results. In a modified BSC, its perspectives and metrics help to achieve the set objectives and report critical outcomes through a strategic map. This research confirms the applicability and flexibility of the BSC and contributes to developing a set of common indicators that reflect the qualitative aspects of activities and enable effectiveness assessment of social medicine activities.